2022
DOI: 10.1111/jcmm.17448
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the multifaceted functions and therapeutic targeting of high mobility group box 1 in metabolic diseases

Abstract: The high mobility group (HMG)-box (HMGB) family belongs to the HMG protein superfamily that plays important roles in modulating chromatin structures. The HMGB family consists of four chromosomal proteins: HMGB1, HMGB2, HMGB3 and HMGB4. HMGB1 is ubiquitously expressed in high abundance (roughly 1 × 10 6 molecules per mammalian cell), whereas HMGB2, 3 and 4 are expressed at lower levels with restricted expression patterns. 1-3 Herein, we summarize the literature reports on the roles of HMGB1 in metabolic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
2
0
4
Order By: Relevance
“…Despite several detrimental factors that can stimulate inflammatory response through diverse pathways mediated by HMGB1, the most important one of the pathways is characterized by the activation of NF-kB. Our results are consistent with the previous study that the inhibition of HMGB1 blocks the TLR4/NF-κB mediated inflammatory response ( Tao et al, 2022 ). Our study indicated that GLC may play an important role in the inhibition of this positive feedback from multiple targets, which is a complicated process that needs further study.…”
Section: Discussionsupporting
confidence: 93%
“…Despite several detrimental factors that can stimulate inflammatory response through diverse pathways mediated by HMGB1, the most important one of the pathways is characterized by the activation of NF-kB. Our results are consistent with the previous study that the inhibition of HMGB1 blocks the TLR4/NF-κB mediated inflammatory response ( Tao et al, 2022 ). Our study indicated that GLC may play an important role in the inhibition of this positive feedback from multiple targets, which is a complicated process that needs further study.…”
Section: Discussionsupporting
confidence: 93%
“…The pro-inflammatory effect of HMGB1 is mainly due to its structural characteristics and derived cellular biological effects ( 9 ). A variety of receptors play a role in HMGB1 signaling, including receptors for advanced non-enzymatic glycation end products (RAGEs) and members of the Toll-like receptors (TLRs) ( 10 ). TLRs bind to RAGEs to amplify the inflammatory response, an important mechanism that promotes atherosclerosis ( 11 ), and HMGB1 is the only known receptor with the highest affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Численні дослідження [8,11,16,22,27] показали, що NF-κB є як фактором, активація якого призводить до виділення амфотерину у позаклітинний простір, так і важливою ланкою сигнального шляху, що активується цим білком після його взаємодії з відповідними рецепторами. Активація NF-κB індукує продукцію та вивільнення багатьох прозапальних медіаторів, що визначає надзвичайно важливу роль цього транскрипційного фактора у розвитку запалення та імунній відповіді.…”
Section: шляхи виділення Hmgb1 механізми дії інгібіториunclassified
“…Крім NF-κB позаклітинний HMGB1 регулює передачу сигналів й через інші шляхи, серед яких MAPK і PI3K [27]. Наприклад, активуючи сигнальний шлях TLR4/MyD88/ NF-κB/p65, позаклітинний HMGB1 може сприя ти пошкодженню ендотеліальних клітин гломерулярного апарату нирок під час вовчакового нефриту [28].…”
Section: шляхи виділення Hmgb1 механізми дії інгібіториunclassified
See 1 more Smart Citation